Studies on the determination of β-D-glucans in Saccharomyces cerevisiae - LIU Xiao-yong; WANG Qiang; LIU Hong-zhi; HU Yong-jin (浙江大学学报. 农业与生命科学版)
Because of the difficulty to disrupt the yeast cell walls, and insolubility of β-D-glucan, the mensuration way for detecting β-D-glucan was a difficult problem. Firstly, vortex-mini-bead disruption way was used to broke the yeast cell walls and the ratio of broken yeast cells reached 95.28%; Secondly, modified sulfuric acid hydrolysis method was adopted to completely release glucose and the recoveries of hydrolysis of β-D-glucan came to 98.76%; Lastly, using GOPOD enzyme way, the content of the yeast β-D-glucan was obtained. The new method for quantitative determination of yeast β-D-glucan was proposed in this basic, the relative standard deviation (RSD) value and the average recovery of the new method were 0.46% and 99.96%, respectively.